Anxiety disorder on women of domestic violence victims - Nilma Zola; Neviyarni Suhaili; Marjohan Marjohan; Ifdil Ifdil; Afdal Afdal (Jurnal Konseling dan Pendidikan, 2021)
Having a harmonious, happy and loving family is everyone’s dream. But few people can make it happen. There are still family members who feel uncomfortable when they are at home. They feel insecure, pressured, unappreciated, and neglected. Domestic violence can affect every family member, wife, husband, children, or other family members. However, the most frequent victims of domestic violence, with the highest number of cases each year, are women. Women who are victims experience various negative affects. Besides impacting the physical, it also impacts the psyche, one of which is anxiety. This paper aims to analyze various research results related to anxiety in women victims of domestic violence. This paper gives a theoretical overview of the research on anxiety in domestic violence victims. Searches in databases relevant to both clinical and consumer behavior literature, such as Scopus, EBSCO, Web of Science – Social Citations Index, Medline, PsycINFO, and Pubmed, were used to conduct a selective review of the literature. The paper examines current thinking on troublesome anxiety disorders in women who have been victims of domestic violence. The literature evaluation allows for the expansion of existing knowledge about domestic violence.